PERLINDUNGAN HUKUM HAK KEPERDATAAN WARGA MASYARAKAT DI ATAS TANAH YANG BERADA DALAM KAWASAN HUTAN BERDASARKAN SK MENTERI KEHUTANAN RI NO. SK. 463/MENHUT-II/2013 DI KOTA BATAM - Lia Nur Aini; Runtung Runtung; Alvi Syahrin; Rosnidar Sembiring (USU LAW JOURNAL, 2014)
ABSTRACT Appointment forests of Riau Islands Province was first carried out on the basis of Forestry Ministerial Decree No. 173 / Kpts-II / 1986 dated June 6, 1986 on the appointment of the Provincial Forest Area In Riau As provincial, Forest Area. The ministerial decision based on the result of an agreement among the various agencies dealing with space management. As a result of agreements between institutions, the Minister of Forestry is better known by the term forest Forest Land Use Agreement (TGHK). But in doing development does not follow the BP Batam Forestry Ministerial Decree No. 173 / Kpts-II / 1986 and Minister of Forestry Decree No. 47 / Kpts-II / 1987. On June 27, 2013, the Ministry of Forestry issued a decree, the Minister of Forestry Decree No. 463 / Menhut-II / 2013, which resulted in several regions in Batam which has built the existing public facilities such as ports, housing, residential areas, shopping malls, business centers and industrial center that has been granted permission by the BP Batam, through Decree 463/2013 is designated as forest area and forest zone status yet Other (APL) which causes doubts for the community will be the status of legal certainty of land rights that they have, this resulted Decree 463/2013 is being debated in the Riau Islands. Communities, businesses, and even traditional leaders in Riau Islands protest. Keyword : legal protection, Civil rights, Forest